Effect of homogenization and microfluidization on physicochemical and rheological properties of mayonnaise. (23rd February 2021) - Kadian, Drishti; Kumar, Anit; Badgujar, Prarabdh C.; Sehrawat, Rachna
Abstract: Application of both homogenization and microfluidization offer remarkable reformations in the structures of food. In this research, the outcome of the homogenization and microfluidization on the emulsion of mayonnaise and resultantly on the rheological and sensory attributes of the mayonnaise was evaluated and compared. Implementation of individual processes was analyzed with regard to rheological properties and physicochemical parameters by preparing samples with and without addition of stabilizers. Mayonnaise samples showed thixotropic behavior and then categorized as shear thinning (Pseudoplastic liquid) showing yield stress. Irrespective of sample testing parameters such as different temperatures and shear rates, all samples revealed shear thinning characteristics. The viscosity of microfluidized sample with or without stabilizer was significantly increased ( p  < .05) as judged against the homogenized sample at both temperatures (20°C and 40°C). The storage modulus of all samples was higher as compared with the loss modulus which shows elastic nature of the mayonnaise. Power law and Weltman model were studied to explain the rheological behavior of the mayonnaise and both models were found best suited. Experimental values illustrated through attempted models very well contribute to future studies on the product and process development. As per the current literature, microfluidization can be used to achieve quick mayonnaise emulsion with better rheological characteristics and hence superior sensosry attributes. Practical Applications: Stabilizers play a critical role in the development of mayonnaise as an additive or constituent. The present study reveals that high‐pressure homogenization (microfluidization) can be exploited to enhance rheological, physical, and chemical properties of the mayonnaise by influencing interaction between fat (oil) and gums (polysaccharides), eventually increasing viscosity. The quality of mayonnaise is usually judged by its techno‐functional and sensory attributes such as spreadability, mouthfeel, appearance, and flavor. However, spreadability and mouthfeel are two predominant attributes that largely affects acceptability of mayonnaise. Microfluidization, when applied to the mayonnaise resulted in improving spreadiability as well as mouthfeel over conventional method, that is, homogenization. Despite the fact that microfluidizer is used for the emulsion formation, stabilizers are found to be inextricable in mayonnaise preparation. Abstract :